Synthesis and Characterization of Novel Terpolymers as Viscosity Index Improvers Using Industrial Waste for Iraqi Lubricating Oil - AL-Malki, Ziyad Tarik; Khalaf, Moayad Naeem (Universitas Gadjah Mada, 2024)
The potential utilization of industrial waste, specifically polyethylene wax, to enhance the efficiency of alkyl acrylate polymers as viscosity index improver (VII) additives in lubricating compositions has been investigated. Four terpolymers (w1, w2, w3, and w4) were synthesized via free radical polymerization, incorporating hexyl acrylate, 1-tetradecene, and industrial waste-sourced polyethylene wax at varying molar ratios. These terpolymers were characterized through gel permeation chromatography (GPC) for molecular weight determination, Fourier transform infrared spectroscopy (FTIR), proton nuclear magnetic resonance (1H-NMR) spectroscopy for chemical structure analysis, and thermal gravimetric analysis (TGA) for thermal stability assessment. The study evaluated the efficiency of these terpolymers as viscosity index improvers (VII) in combination with free additives Iraqi lubricating oil (base oil 60). Our results demonstrate the feasibility of significantly enhancing the efficiency of viscosity improvers through the utilization of industrial waste, with improvements proportional to terpolymer concentration. The terpolymer w3, characterized by a balanced molar ratio of 1:1:1, exhibiting the highest degree of efficacy, which gave VI of 206 at 5 wt.% concentration compared with free additive lubricating oil, which gives VI of 98. This study offers promising insights into the sustainable use of industrial waste to improve lubricating compositions.